Down-regulation of miR-133a and miR-539 are associated with unfavorable prognosis in patients suffering from osteosarcoma. Issue 1 (December 2015) - Mirghasemi, Alireza; Taheriazam, Afshin; Karbasy, Seyyed; Torkaman, Ali; Shakeri, Mohammadreza; Yahaghi, Emad; Mokarizadeh, Aram
Abstract Background MicroRNAs (miRNAs) play key roles in cancer development and progression. The purpose of the present study was to determine the expression levels of miR-133a and miR-539 in osteosarcoma patients and to further investigate the clinicopathological, and prognostic value of these miRNAs. Methods The expression levels of miR-133a and miR-539 were determined by qRT-PCR. Associations between miRNAs expressions and various clinicopathological characteristics were analyzed. Survival rate was determined with Kaplan–Meier and statistically analyzed with the log-rank method between groups. Survival data were evaluated through multivariate Cox regression analysis Results Our findings revealed that the miR-133a expression was significantly decreased in clinical osteosarcoma tissues compared to adjacent normal bone tissues. The expression level of miR-539 was decreased in clinical osteosarcoma tissues as compared to those adjacent normal tissues. Low expressions of miR-133a and miR-539 were significantly association with advanced TNM stage (P = 0.002; P = 0.001), and metastasis or recurrence (P = 0.001; P = 0.01). Furthermore, Kaplan–Meier survival analysis and log-rank test showed that the low expressions of miR-133a and miR-539 were correlated with the reduced overall survival of osteosarcoma patients. Multivariate Cox proportional hazards model showed that decreased expressions of miR-133a and miR-539 (P = 0.007; P = 0.02), TNM stage (P = 0.001; P = 0.002), and metastasis or recurrence (P = 0.005; P = 0.026) were independent prognostic markers of overall survival of patients. Conclusion These results suggest that decreased miR-133a and miR-539 expressions may participate in the progression of osteosarcoma. Together, these results showed that miR-133a and miR-539 may have their role in both progression and prognosis of osteosarcoma.